Annexin A6 improves anti‐migratory and anti‐invasive properties of tyrosine kinase inhibitors in EGFR overexpressing human squamous epithelial cells. (9th January 2020) - Hoque, Monira; Elmaghrabi, Yasmin A.; Köse, Meryem; Beevi, Syed S.; Jose, Jaimy; Meneses‐Salas, Elsa; Blanco‐Muñoz, Patricia; Conway, James R. W.; Swarbrick, Alexander; Timpson, Paul; Tebar, Francesc; Enrich, Carlos; et al.
Abstract : Annexin A6 (AnxA6), a member of the calcium (Ca 2+ ) and membrane binding annexins, is known to stabilize and establish the formation of multifactorial signaling complexes. At the plasma membrane, AnxA6 is a scaffold for protein kinase Cα (PKCα) and GTPase‐activating protein p120GAP to promote downregulation of epidermal growth factor receptor (EGFR) and Ras/mitogen‐activated protein kinase (MAPK) signaling. In human squamous A431 epithelial carcinoma cells, which overexpress EGFR, but lack endogenous AnxA6, restoration of AnxA6 expression (A431‐A6) promotes PKCα‐mediated threonine 654 (T654)–EGFR phosphorylation, which inhibits EGFR tyrosine kinase activity. This is associated with reduced A431‐A6 cell growth, but also decreased migration and invasion in wound healing, matrigel, and organotypic matrices. Here, we show that A431‐A6 cells display reduced EGFR activity in vivo, with xenograft analysis identifying increased pT654‐EGFR levels, but reduced tyrosine EGFR phosphorylation compared to controls. In contrast, PKCα depletion in A431‐A6 tumors is associated with strongly reduced pT654 EGFR levels, yet increased EGFR tyrosine phosphorylation and MAPK activity. Moreover, tyrosine kinase inhibitors (TKIs; gefitinib, erlotinib) more effectively inhibit cell viability, clonogenic growth, and wound healing of A431‐A6 cells compared to controls. Likewise, the ability of AnxA6 to inhibit A431 motility and invasiveness strongly improves TKI efficacy in matrigel invasion assays. This correlates with a greatly reduced invasion of the surrounding matrix of TKI‐treated A431‐A6 when cultured in 3D spheroids. Altogether, these findings implicate that elevated AnxA6 scaffold levels contribute to improve TKI‐mediated inhibition of growth and migration, but also invasive properties in EGFR overexpressing human squamous epithelial carcinoma. Abstract : The scaffolding protein annexin A6 (AnxA6) inhibits oncogenic epidermal growth factor receptor (EGFR) activity in human squamous epithelial A431 cells. This study shows that AnxA6 reduces EGFR activity in A431 tumors in vivo . Moreover, AnxA6 upregulation improves growth‐inhibitory, anti‐migratory, and anti‐invasive properties of tyrosine kinase inhibitors (gefitinib, erlotinib). These findings could be relevant for the treatment of epidermoid cancers, such as non‐small‐cell lung cancers or head and neck cancers.